DICCIO BUSINESS FRAMEWORK SEBAGAI STRATEGI PERTUMBUHAN UMKM (USAHA MIKRO, KECIL DAN MENENGAH) DI INDONESIA - Deni; Saraswati, Koleta; Setiawan, Yuli; Stefhani, Yosi; Wahyono, Agus (Jurnal Manajemen, 2025)
MSMEs in Indonesia play an essential role in the economy but still face challenges in terms of growth and competitiveness. This research discusses the implementation of the DICCIO Business Framework for the development of MSMEs in Indonesia. DICCIO's business framework includes four main pillars: digital marketing, cause collaboration, influencer marketing, and omnichannel marketing. The research objective is to analyze the framework's effectiveness in improving the growth and competitiveness of MSMEs. The research method used is qualitative to obtain an in-depth understanding of the framework's application. Data analysis is done descriptively, and secondary data is obtained from relevant agencies such as BPS, BI, and the Ministry of Cooperatives and SMEs. The study shows that the DICCIO Business Framework can help MSMEs develop effective Digital Marketing strategies. Implementing digital and influencer marketing has increased MSMEs' visibility and market reach. Meanwhile, cause-collaboration and omnichannel marketing can increase consumer trust and sales. In conclusion, the DICCIO Business Framework is an effective strategy to drive the growth and competitiveness of MSMEs in the digital era. This framework can be recommended to be implemented by MSMEs in Indonesia.